Practical grounding, bonding, shielding and surge protection - Vijayaraghavan, G. (Newnes, 2004)
This book will allow you to gain practical skills and know-how in grounding, bonding, lightning & surge protection. Few topics generate as much controversy and argument as that of grounding and the associated topics of surge protection, shielding and lightning protection of electrical and electronic systems. Poor grounding practice can be the cause of continual and intermittent difficult-to-diagnose problems in a facility. This book looks at these issues from a fresh yet practical perspective and enables you to reduce expensive downtime on your plant and equipment to a minimum by correct application of these principles.